Determinants of Menstrual Hygiene Associated with Knowledge, Attitude and Practice among School-Going Adolescent Girls in Banke District, Nepal (Voice: A Biannual & Bilingual Journal, 2025)
Menstruation is a natural biological process showing periodic discharge of blood and ovum due to hormonal changes in the female reproductive system every month till the reproductive aged, and it signifies physical maturity. This study aimed to assess the factors associated knowledge, attitude, and practices regarding menstrual hygiene among school-going adolescent girls in Banke district, Nepal. A school based cross-sectional study was used, and multistage random sampling technique was employed to select 430 school going adolescent girls from eight schools in March to April, 2025. Chi-square test was applied for bi-variate analysis. A multinomial logistic regression model was used to determine statistically significant factors.The findings revealed that 71.2%, 79.8% and 54% of participants had good knowledge, positive attitude and good menstrual hygiene practices. In comparison to good knowledge, respondents with older age were 1.68 times, mothers with secondary education were 4.05 times, respondents who received information from social media were 4.22 times more likely to had moderate knowledge. As compared to poor to good knowledge, respondents who did not track mensural cycle were 3.15 times, respondents who felt no influence from menstrual portrayals were 7.14 times more likely to have poor knowledge, whereas mensuration information from social media is 75% less likely to have poor knowledge. Respondents whose mothers were illiterate being 5.36 times more likely to report poor attitudes, and adolescents whose fathers were illiterate being 68% less likely to report good attitudes compared to those whose mothers and fathers had a basic level of schooling. The respondents from private schools were 75% less likely to report a poor practice compared to those from government schools. Students from urban residence had 2% less likely to have poor practice, and private school students had 2.68 times better practice than government school students. Further, students with no cultural restrictions had 1.95 times better practice than students with cultural restrictions.The parents’ education showed a significant influence on their children's knowledge and attitudes of menstrual hygiene. Also, cultural restrictions harmed menstrual hygiene. The study identified a notable gap between knowledge and attitude versus actual practices. Thus, special attention should be given to students from government schools, from rural areas, and those facing cultural restrictions to improve menstrual hygiene practices.